Isolation and Characterization of a Lactose-Binding Lectin from Ocimum sanctum - Praveen Kumar Vemuri, Bhavana Talluri, Ananya Sharma, Geethika Akkala, Vijaya Lakshmi Bodiga (Journal of Applied Pharmaceutical Science, 2015)
A novel lectin has been isolated from Ocimum sanctum and purified to homogeneity by gel filtration chromatography, which eluted as a single symmetrical peak from a Biogel P-100 column with a molecular mass of 66 kDa. The lectin had a special agglutinating activity with human erythrocytes at a minimum concentration of 0.7 ug/ml. The lectin was stable in the pH range 5-12 and temperature 80 °C for 30 min. Ocimum sanctum had shown highest agglutinating activity at pH7 and 250C temperature after one hour incubation. Of the various sugars tested, even at 1000 mM sugar concentration, no inhibition was observed. The isolated lectin was found to be lactose-biding lectin sugar moieties and contain 2.6 mg/ml total sugar and 9.3 mg/ml of total protein.
Keywords: Lectin, Blood group, Glycobiology ELISA, Agglutination, Ocimum sanctum.